2022
DOI: 10.1186/s12943-022-01515-x
|View full text |Cite
|
Sign up to set email alerts
|

Engineered exosomes as an in situ DC-primed vaccine to boost antitumor immunity in breast cancer

Abstract: Background Dendritic cells (DCs) are central for the initiation and regulation of innate and adaptive immunity in the tumor microenvironment. As such, many kinds of DC-targeted vaccines have been developed to improve cancer immunotherapy in numerous clinical trials. Targeted delivery of antigens and adjuvants to DCs in vivo represents an important approach for the development of DC vaccines. However, nonspecific activation of systemic DCs and the preparation of optimal immunodominant tumor anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(138 citation statements)
references
References 70 publications
2
116
0
Order By: Relevance
“…In situ DC vaccines with tumour cell-derived sEVs as carriers activate type 1 conventional DCs (cDC1s) and cross-prime tumour-reactive CD8+ T-cell responses. A potent tumour-suppressive effect has been observed in mouse xenograft models of TNBC and patient-derived tumour organoids [ 131 ].…”
Section: Clinical Applications Mediated By Sevsmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ DC vaccines with tumour cell-derived sEVs as carriers activate type 1 conventional DCs (cDC1s) and cross-prime tumour-reactive CD8+ T-cell responses. A potent tumour-suppressive effect has been observed in mouse xenograft models of TNBC and patient-derived tumour organoids [ 131 ].…”
Section: Clinical Applications Mediated By Sevsmentioning
confidence: 99%
“…In situ DC vaccines with tumour cellderived sEVs as carriers activate type 1 conventional DCs (cDC1s) and cross-prime tumour-reactive CD8+ T-cell responses. A potent tumour-suppressive effect has been observed in mouse xenograft models of TNBC and patient-derived tumour organoids [131]. The sEVs of breast cancer can provide a measure of organtropism, such as specific exosomal integrin combinations (there is a link between exosomal α6β4 and α6β1 integrins and lung metastasis/exosomal αvβ5 integrin with liver metastasis/exosomal αvβ3 integrin with brain metastasis).…”
Section: Sevs As a Novel Therapeutic Optionmentioning
confidence: 99%
“…Due to the effective role of DCs, cell-based vaccine emerged as a promising option in tumor treatment. According to Huang et al( Huang et al, 2022 ), a in situ DC-primed vaccine drastically facilitated CD8 + T cell responses, which resulted in obvious tumor suppression in TNBC mouse xenograft model and patient-derived tumor organoids. In our study, we co-cultured BMDCs with Huaier-treated or -untreated 4T1 cells, the results revealed that TNBC cells could provoke the activation of DCs in the presents of Huaier.…”
Section: Discussionmentioning
confidence: 99%
“…ICD can enhance tumor antigen exposure, promote the release of immune-stimulating tumor cell content, and facilitate the uptake of dying tumor cells by DCs. Huang et al constructed a combination of TLR3 agonist Hiltonol and ICD inducer ELANE to engineer TEXs that can activate DCs in situ in a mouse xenograft model of poorly immunogenic triple-negative breast cancer and tumor organs derived from patients with hot tears; both produced effective tumor suppression [ 104 ]. In conclusion, engineered tumor-cell-derived membrane vesicles have a promising application in developing anti-tumor vaccines due to their great advantage of carrying tumor-specific antigens.…”
Section: The Application Of Tumor Cell-derived Membrane Vesicles To P...mentioning
confidence: 99%